Daya Terima Nugget Tempe, Ikan dan Havermout (Temfishmout) sebagai Snack Rendah Kolesterol - Yunita - Nazarena; Terati Terati; Eliza Eliza; Imelda Telisa; Sriwiyanti Sriwiyanti (Jurnal Sehat Mandiri, 2025)
Tempefishmout nuggets are nuggets made from tempeh, patin fish and oatmeal. The composition of the three main ingredients is rich in nutrients, high in fiber and low in cholesterol. Fish and tempeh are local foods that are easy to obtain and affordable. The purpose of this study was to determine the acceptability of tempefishmout nuggets. The type of research used was experimental research with a completely randomized non-factorial design. This research was conducted from April to November 2022 at the Food Technology Lab of Poltekkes Palembang. There are 5 Formulas used in this study, namely: F1 (80% tempeh: 15% catfish: 5% oatmeal flour), F2 (60% tempeh: 30% catfish: 10% oatmeal flour), F3 (50% tempeh: 35% catfish: 15% oatmeal flour), F4 (40% tempeh: 40% catfish: 20% oatmeal flour), F5 (20% tempeh: 60% catfish: 20% oatmeal flour) with three repetitions and using the deep frying method. The equipment used is a fryer, food scales, stoves and thermometers. The acceptance test was carried out by 30 semi-trained panelists. The results of the study showed that Formula F5, which was most preferred by panelists, had the highest scores for color (4.80 ± 0.03 b), aroma (4.60 ± 0.03 b), taste (4.52 ± 0.11c), and texture (4.32 ± 0.17 b).